2014
DOI: 10.1109/tmi.2013.2293974
|View full text |Cite
|
Sign up to set email alerts
|

Low-Rank Modeling of Local <formula formulatype="inline"> <tex Notation="TeX">$k$</tex></formula>-Space Neighborhoods (LORAKS) for Constrained MRI

Abstract: Recent theoretical results on low-rank matrix reconstruction have inspired significant interest in low-rank modeling of MRI images. Existing approaches have focused on higher-dimensional scenarios with data available from multiple channels, timepoints, or image contrasts. The present work demonstrates that single-channel, single-contrast, single-timepoint k-space data can also be mapped to low-rank matrices when the image has limited spatial support or slowly varying phase. Based on this, we develop a novel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(76 citation statements)
references
References 50 publications
0
76
0
Order By: Relevance
“…Low-rank modeling of local k-space neighborhoods (LORAKS) works by reconstructing k-space data using low rank matrix completion [135,136]. The reconstruction attempts to find a solution that is both consistent with the undersampled data and also satisfies two special properties.…”
Section: Phase-constrained Parallel Imagingmentioning
confidence: 99%
“…Low-rank modeling of local k-space neighborhoods (LORAKS) works by reconstructing k-space data using low rank matrix completion [135,136]. The reconstruction attempts to find a solution that is both consistent with the undersampled data and also satisfies two special properties.…”
Section: Phase-constrained Parallel Imagingmentioning
confidence: 99%
“…The linear dependencies between the Fourier coefficients exploited the in structured low-rank matrix priors result from a variety of assumptions, including continuous domain analogs of sparsity [3], [6], [8], [9], correlations in the locations of the sparse coefficients in space [8], [9], multi-channel sampling [2], [10], [11], or smoothly varying complex phase [4]. For example, the LORAKS framework [4] capitalized on the sparsity and smooth phase of the continuous domain image using structured low-rank priors, which offers improved reconstructions over conventional ℓ 1 recovery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the LORAKS framework [4] capitalized on the sparsity and smooth phase of the continuous domain image using structured low-rank priors, which offers improved reconstructions over conventional ℓ 1 recovery. Similarly, we have shown that the Fourier coefficients of continuous domain piecewise constant images whose discontinuities are localized to zero level-set of a bandlimited function satisfy an annihilation relationship [9]; their recovery from undersampled Fourier measurements translates to a convolutional structured low-rank matrix completion problem [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a series of images with the same anatomy but different image contrast is acquired in contrast enhanced MR angiography, methods that exploit the spatiotemporal correlation of the dynamic image series, such as keyhole, various k-t (K-space domain and time doman) methods, and low-rank methods, can also be applied [1119]. Promising results in contrast enhanced MR angiography have been achieved using parallel imaging, compressed sensing and low-rank methods or the combination of these methods [2029]. …”
Section: Introductionmentioning
confidence: 99%